Implementasi hak asasi manusia dalam regulasi keperdataan Islam di Indonesia mengenai keterlantaran anak - Rajeib, Jazwan (Maliki Interdisciplinary Journal, 2024)
Human rights are basic rights that every human being has from birth until death. In the universal aspect, humans are guaranteed by the state the freedom to live their lives which of course does not violate the regulations that have been determined. Not only the state, in the teachings of the Islamic religion there is freedom that every servant has in carrying out his life in accordance with religious law. However, in reality, there are still many young children who are neglected and far from their parents’ care. The increase in divorce and the lack of readiness of husbands and wives when starting a family is a problem serious enough to cause children to become neglected. Therefore, the human rights of neglected children are given little attention by the government. Even though civil law, criminal law and even Islamic civil law have made regulations regarding human rights and protection for neglected children. This research includes a systematic approach by means of in-depth analysis of the structure, methodology, findings and conclusions presented in the sources reviewed. The results of this research are that abandoned children still have the same rights and equality before the law, and the government must be more assertive in its concern regarding abandoned children.